2014
DOI: 10.1093/molehr/gau116
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a human subcortical maternal complex

Abstract: Maternal effect genes play essential roles in early embryonic development. However, the mechanisms by which maternal effect genes regulate mammalian early embryonic development remain largely unknown. Recently, we identified a subcortical maternal complex (SCMC) that is composed of at least four proteins encoded by Mater, Floped, Tle6 and Filia and is critical for mouse preimplantation development. The present study demonstrates that human SCMC homologous genes (NLRP5, OOEP, TLE6 and KHDC3L) are specifically e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 38 publications
3
68
0
1
Order By: Relevance
“…For example, Smarca4 (also known as Brg1 ) encodes the catalytic subunit of the SWI/SNF-related complex that is required for chromatin remodeling during zygotic genome activation [15]. Nlrp5 (also known as Mater ) is part of the subcortical maternal complex (SCMC), a conserved subcortical domain in oocytes and zygotes that appears to harbor proteins involved in embryonic development and that has also been detected in human oocytes and embryos [1618]. It has only recently been shown that NLRP5 protein is involved in mitochondrial activation, endoplasmic reticulum localization and calcium homeostasis in oocytes and early embryos [1922].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Smarca4 (also known as Brg1 ) encodes the catalytic subunit of the SWI/SNF-related complex that is required for chromatin remodeling during zygotic genome activation [15]. Nlrp5 (also known as Mater ) is part of the subcortical maternal complex (SCMC), a conserved subcortical domain in oocytes and zygotes that appears to harbor proteins involved in embryonic development and that has also been detected in human oocytes and embryos [1618]. It has only recently been shown that NLRP5 protein is involved in mitochondrial activation, endoplasmic reticulum localization and calcium homeostasis in oocytes and early embryos [1922].…”
Section: Introductionmentioning
confidence: 99%
“…In human, it is found to have physical interactions with Mater/Nlrp5, Floped/Ooep, and Tle6 (31), which may result from different Filia protein structures and alternatively introduced reactive sites. Additionally, SCMC is predominantly localized in the human subcortex of oocyte (31,32), but in mouse, it is also found in the oocyte cytoplasm (33,34). Hence, difference in bovine and ovine Filia protein structures may also affect the molecular interactions between Filia and its partners (SCMC or other unknown proteins), which may probably be the reason of different locations reported for Filia protein in cow and sheep.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, it is currently composed of at least four known oocyte-derived proteins: oocyte-expressed protein (OOEP; also known as Factor Located in Oocytes Permitting Embryonic Development, FLOPED), Transducin-Like Enhancer of Split 6 (TLE6), NLR family, Pyrin domain-containing 5 (NLRP5; also known as Maternal Antigen That Embryos Require, MATER) and KH Domain Containing 3-Like (KHDC3L; also known as ES Cell-Associated Transcript I, ECAT1, C6ORF221 or FILIA) (Zhu et al 2015). These proteins localise to the subcortical region in mouse and human oocytes and pre-implantation embryos are excluded from regions of cell-to-cell contact from the zygote onwards and are devoid from the inner cell mass of the blastocysts (Li et al 2008a).…”
Section: The Subcortical Maternal Complexmentioning
confidence: 99%